Mini-massive open online course (MOOC) on food environments for healthy sustainable diets, co-developed by A4NH researchers and partners - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The course is designed for professionals from government, ministries and NGOs who are aware of the need for food environment interventions.